2011
DOI: 10.5897/jabsd11.027
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of fruit yield and it’s contributing characters in tomato (Solanum lycopersicom)

Abstract: Tomato is a premier vegetable crop of round the year and one of the prominent eco-industrial crops of India generating sizeable employment. The present study which consisted 10 genotypes was evaluated in randomized block design replicated thrice at Regional Agricultural Research Station-Ujjain during Rabi 2007 to 2008. The variation was maximum (424 to 825 qtl/ha) for fruit yield and minimum for fruit width (4.1 to 5.6 cm). The magnitude of genotypic and phenotypic coefficient of variation was higher for numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 4 publications
15
24
0
2
Order By: Relevance
“…Similar findings were also reported by Golani et al, (2007), Dar and Sharma (2011), Kaushik et al, (2011), Rani and Anitha (2011) and Chernet et al, (2013.…”
Section: Phenotypic Coefficient Of Variationsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar findings were also reported by Golani et al, (2007), Dar and Sharma (2011), Kaushik et al, (2011), Rani and Anitha (2011) and Chernet et al, (2013.…”
Section: Phenotypic Coefficient Of Variationsupporting
confidence: 80%
“…Yield per plant showed the greatest range of variation as reported by Haydar et al, (2007), Mehta and Asati (2008), Ghosh et al, (2010), and Kaushik et al, (2011), followed by proline content, number of fruits per plant, stomatal frequency, fruit volume and number of leaves per plant (Table 2).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Relatively higher difference was noted between GCV and PCV values in the traits: Flowers/cluster Fruits/cluster and Fruit weight and relatively low difference was noted for GCV and PCV value in the traits: Fruit diameter, Fruit length and fruits/plant. Khanom et al [4] also found smaller difference between GCV and PCV value for the trait fruits/length while Kaushik et al [14] found small difference between GCV and PCV for fruit diameter. Moderate difference was noted between GCV and PCV in the parameter yield/plant.…”
Section: Resultsmentioning
confidence: 99%
“…The range recorded for plant height (78.00-171.00) number of days taken to first flowering (31.33-40.6 Supe et al, (2006), Sharma et al,.(2006),. Lal et al, (1991), Bharti et al, (2002), Brar et al, (2000, Mohanty (2002), Kaushik et al, (2011), Islam et al, (2012. Rahaman et al, (2012), Vinod Kumar et al, (2013), Dar and Sharma (2011), Rani and Anitha (2011), Golani et al, (2007 Ahmed et al, (2006), Mahesha et al,.Joshi and Singh,.…”
Section: Resultsmentioning
confidence: 99%